Setting of import tolerances for mandipropamid in papayas. (11th January 2023) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Castellan, Irene; Del Aguila, Monica; Ferreira, Lucien; Santonja, German Giner; Greco, Luna; Jarrah, Samira; Leuschner, Renata; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Syngenta Crop Protection AG submitted a request to the competent national authority in Austria to set an import tolerance for the active substance mandipropamid in papayas. The data submitted in support of the request were found to be sufficient to derive an maximum residue level (MRL) proposal of 0.8 mg/kg for papayas. Adequate analytical methods for enforcement are available to control the residues of mandipropamid on the commodity under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that long‐term intake of residues resulting from the use of mandipropamid according to the reported agricultural practice is unlikely to present a risk to consumer health. The reliable end points, appropriate for use in regulatory risk assessment are presented.